Humanized dental surgical treatment in a patient with intellectual disability – Case report (Research, Society and Development, 2021)
The aim of this study was to describe a clinical case of a teenager with mild intellectual disability, with accumulated surgical need. Male patient, faioderma, 17 years old, 1.86 cm tall, 60 kg, with mild intellectual disability, enrolled in the public school system. The teenager had an accumulated dental surgical need, referring to root debris, which according to the mother, was his main complaint. During the anamnesis, she reported that she did not face difficulties with the adolescent in their daily oral hygiene, that he makes continuous use of the medication Risperidone (1mg) and that he has always been a collaborator in previous dental clinical treatments, his main problem being “fear of the needle ”in the surgical act. Through a humanized approach, the surgical procedure was resolutive and performed on an outpatient basis, under local anesthesia with full participation of the patient, making him proactive in the actions performed during the dental process, as well as being able to overcome his initial fear.